Do people behave in experiments as in the field? Evidence from donations - Matthias Benz; Stephan Meier (Federal Reserve Bank of Boston, 2006)
Laboratory experiments are an important methodology in economics, especially in the field of behavioral economics. However, it is still debated to what extent results from laboratory experiments can be applied to field settings. One highly important question with respect to the external validity of experiments is whether individuals act the same in experiments as they would in the field. This paper presents evidence on how individuals behave in donation experiments and how the same individuals behave in a naturally occurring decision situation on charitable giving. The results show that behavior in experiments is correlated with behavior in the field. The results are robust to variations in the experimental setting, and the correlation between experimental and field behavior is between 0.25 and 0.4. We discuss whether this correlation should be interpreted as strong or weak and what consequences the findings have for experimental economics.
Keywords: C91; C93; D01; D64; 330; Experiments; external validity; methodology; charitable giving